Curricular adaptation: alternatives of pedagogical support in the inclusive education - Lucia Pereira Leite; Sandra Eli Sartoreto Martins (Universidade Federal de Santa Maria (UFSM), 2010)
The organization of the inclusive education is a slow and complex process, which has the necessity of investments in supports for all the scholar team. Aiming at spreading one of the actions carried out for the promotion of the inclusive educational practices in a municipal education system in a western city in the state of São Paulo, this paperwork has the objective of presenting an elaborated manual of orientations for the implementation of the individual curricular adaptations (ACIs) for students who demand special educational necessities.(NEEs). The material was constituted on the basis of three data sets: 1) tabulation of the evaluations of the curricular adaptations already made; 2) the literature review; 3) analysis of the themes which have emerged during case discussion meetings mediated by the researchers with teachers from the Specialized Pedagogical Support Service (SAPE), with teachers and administrators from the common education system and the technical-pedagogical team. The final version of the manual contemplates the theoretical-operational aspects about the themes: flexibility and curricular adequation, inclusive education, definitions of NEEs, how SAPE works; and it finishes with a model proposal of ACI. It is expected that the spreading of this material can subside new curricular propositions for students with deficiency that are very distant from the academic level expected for the current scholar year.